PENDAMPINGAN SISTEM PENGELOLAAN KEUANGAN BERBASIS SPREADSHEET BAGI GURU MI DARUSSALAM JATIGUWI - Sa'diyah, Khalimatus; Suharti, Profiyanti Hermien; Hidayati, Mutia Devi; Iswara, M. Agung Indra (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
MI Darussalam Jatiguwi is one of the MI’s in Malang Regency. Many problems are faced by the institution, one of which is the limited number and competence of teachers or teaching staff and the lack of use of information technology to support activities financial management system in elementary school. The purpose of implementing this Community Service Activity (PkM) is the revitalization and development of MI Darussalam teachers related to a SpreadSheet-based financial management system mentoring workshop. The implementation of PkM is carried out by giving live lectures and demonstrations of using applications to manage madrasah finances. The PkM activity was held in the MI Darussalam Jatiguwi building and was attended by the PkM Team and students of the Chemical Engineering Department as well as teachers and staff of MI Darussalam Jatiguwi. This PkM activity pays attention to the health protocol, namely the participants involved are measured their body temperature, before entering the room clean their hands and must wear masks during the activity. The event started with an opening by the Chairman of the MI Darussalam Foundation, followed by remarks by representatives of the PkM Team, a symbolic handover of computer grants and the provision of materials. Participants participated enthusiastically.